Sports experience and religious experience. Elements of analysis - Machoń, Henryk (Hybris, 2012)
The phenomenon of sport, especially its popularity and significance, strongly marks the contemporary world. This text is an attempt to describe sports experience (especially football) as a value for a fan experiencing it. It is not an analysis of sport in the philosophical perspective usually concentrating on its ethical or anthropological aspects. That is why the author analyses here, among other things, its identity, aesthetic and egalitarian character, touching upon such important phenomena as patriotic feelings in the context of sport, its media dimension or the problems with stadium hooligans. Finally, to emphasize the research problem outlined in this way, the author discusses the thesis of striking similarities between sports experience and religious experience formulated repeatedly in the present debate over contemporary forms of global secularization.]